Reorganizing the Library for the Future - Geleijnse, Hans (REBIUN, 2007)
Overview.Challenges for Libraries.Why one integrated service?.Goals of new service organisation.The process.Organisation.Staff changes and personnel development.Towards a more user oriented organisation.Innovations.Evaluation and Conclusions
Keywords: Gestión de bibliotecas; Orientación a usuarios; Recursos humanos